Ports and climate uncertainty: An economic imperative for India. (3rd July 2021) - Thakur, Saurabh
ABSTRACT: Seaports are an indispensable asset in interconnected and interdependent global supply chains. Their complex infrastructural and operational systems and critical foreland and hinterland networks make ports a vital nodal point in the economic progress of nations at large, and the coastal urban agglomerations in particular. These critical maritime assets are currently under threat from the disruptive impacts of anthropogenic climate change, such as sea-level rise and intensifying extreme weather events. The economic losses from these impacts will span a wide range, from hard infrastructural damages to operational delays in supply chain management. Incorporating climate resilience in existing and new port infrastructure remains a complex challenge that will require port authorities to confront the problem of climate uncertainty and its socio-economic implications. This article focuses on seaports in the Indian context to highlight the complex threats of climate change. It examines the main debates on climate uncertainty and policymaking, path dependencies in port planning, global best practices, knowledge gaps and strategies that will be critical for Indian ports to better confront climate change induced disruptions in the near future.